Record of soft scale (Coccus hesperidium Linn.) and its parasite (Coccophagus ceroplastae (Howard) on cardamom (Elettaria cardamomum Maton) - KUMARESAN, JASVIR SINGH, TAMIL SELVAN, D (Journal of Spices and Aromatic Crops, 1994)
A soft scale (Coccus hesperidium) is reported to occur on cardamom (Elettaria cardamomum) for the first time from Saklespur, Karnataka, India. The pest was parasitised by a hymenopteran, Coccophagus ceroplastae in the field.